Figurative Language Analysis of Melanie Martinez’s Lyrics Songs from Cry Baby Album Deluxe Edition - Wahyu, Wahyu; Dwi Syaputri, Komala (PT ARRUS Intelektual Indonesia, 2023)
This research is focused on the figurative language used in Melanie Martinez’s Cry Baby Album Deluxe Edition. This research aims the types of figurative language, the implied meaning, and the most dominant type oof figurative language. Descriptive method is used in this research and used the documentation technique for obtained the data. The results from this research are expected to give the readers more knowledge about types of figurative language and the meaning from it. There are 10 types of figurative language being used in Melanie Martinez’s lyrics songs from Cry Baby Album Deluxe Edition which are dominated by Imagery 25%, Metaphor 21, 2%, Simile 13, 5%, Personification 11, 5%, Hyperbole 7, 7%, Irony 7, 7%, Allusion 5, 8 %, Symbol 3, 8%, Apostrophe 1, 9% and Paradox 1, 9%.